2020
DOI: 10.1016/j.cub.2020.05.032
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Crumbs Complex Defines a Distinct Polarity Domain Apical of Epithelial Tight Junctions

Abstract: Epithelial apico-basal polarity is established through the asymmetric cortical distribution of the Par, Crumbs and Scribble polarity modules. Apical (Par and Crumbs) and basolateral (Scribble) polarity modules overlap at the apicallateral border, which, in mammals, is defined by the apical junctional complex (AJC). The AJC is composed of tight junctions (TJ) and adherens junctions (AJ) and plays fundamental roles in epithelial morphogenesis and plasticity.However, the molecular composition and precise sub-junc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 97 publications
(118 reference statements)
4
97
1
Order By: Relevance
“…Our finding that PAR3 localizes at the TJ confirms previous observations using electron microscopy in rat small intestine (Izumi et al, 1998) and MDCK cells . One recent study found a small fraction of PAR3 at the level of the adherens junction (Tan et al, 2020). Even though STED allows for much larger volume to be probed compared to electron microscopy, we did not observe PAR3 basal of the TJ.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Our finding that PAR3 localizes at the TJ confirms previous observations using electron microscopy in rat small intestine (Izumi et al, 1998) and MDCK cells . One recent study found a small fraction of PAR3 at the level of the adherens junction (Tan et al, 2020). Even though STED allows for much larger volume to be probed compared to electron microscopy, we did not observe PAR3 basal of the TJ.…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies were largely based on biochemical approaches. The first interactions found defined canonical polarity protein complexes, while subsequent studies highlighted the numerous potential interactions that can be found with such approach, between polarity proteins of different complexes, (Assémat et al, 2008;Bhat et al, 1999;Hurd et al, 2003;Joberty et al, 2000;Lemmers et al, 2004;Lin et al, 2000;Makarova et al, 2003;Roh, Makarova, et al, 2002) as well as between polarity proteins and other interactors (Chen & Macara, 2005;Itoh et al, 2001;Médina et al, 2002;Michel et al, 2005;Takekuni et al, 2003;Tan et al, 2020). Altogether these studies provide a complex potential model of molecular interactions.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fan et al [22] demonstrated that PTPN13 can dephosphorylate junctional adhesion molecule-A (JAM-A), a transmembrane component of tight junctions, leading to their stabilization. Then, analysis of the interactome of different cell junctions showed that in epithelial cells, PTPN13 is part of the apical marginal zone and interacts with tight junctions and cytoskeleton molecules [94].…”
Section: Emt Cell Migration and Invasionmentioning
confidence: 99%